2015
DOI: 10.1007/s11547-015-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

X-ray, CT and DXA study of bone loss on medieval remains from North-West Italy

Abstract: The differences observed in the BMD values may be related to the different lifestyle of the rural population, i.e. more dietary calcium intake, more sun exposure and vigorous physical activity, compared to that of the privileged individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Another example from medieval Italy (8 th -13 th , 17 th centuries) is a case of increased BMD in lumbar vertebrae and femoral samples analysed using computed tomography (CT) and DXA in individuals of low SES [124]. The elevated data agreed with evidence for an increase in calcium consumption and higher physical activity in the low SES group [124]. This study particularly highlights that the direction of SES effect on bone health cannot be easily predicted.…”
Section: Modern Perspective Through Social Epidemiology and Epigenetimentioning
confidence: 52%
See 1 more Smart Citation
“…Another example from medieval Italy (8 th -13 th , 17 th centuries) is a case of increased BMD in lumbar vertebrae and femoral samples analysed using computed tomography (CT) and DXA in individuals of low SES [124]. The elevated data agreed with evidence for an increase in calcium consumption and higher physical activity in the low SES group [124]. This study particularly highlights that the direction of SES effect on bone health cannot be easily predicted.…”
Section: Modern Perspective Through Social Epidemiology and Epigenetimentioning
confidence: 52%
“…in [127] the authors acknowledge limited written SES records). Another example from medieval Italy (8 th -13 th , 17 th centuries) is a case of increased BMD in lumbar vertebrae and femoral samples analysed using computed tomography (CT) and DXA in individuals of low SES [124]. The elevated data agreed with evidence for an increase in calcium consumption and higher physical activity in the low SES group [124].…”
Section: Modern Perspective Through Social Epidemiology and Epigenetimentioning
confidence: 70%
“…Previous research on bone loss in archeological populations in Norway (Holck, 2007; Mays et al, 2006; Turner‐Walker et al, 2001; Turner‐Walker, Syversen, & Mays, 2000) and the other Scandinavian countries (Bennike & Bohr, 1990; Ekenman et al, 1995; Poulsen et al, 2001) has detected a varied pattern with regards to age‐related bone loss. To our knowledge, the impact of SES on BMD and bone loss has not previously been examined in Scandinavia but has been addressed in several other international studies (Borre et al, 2015; Di Stefano et al, 2012; Mays, 1996; Miszkiewicz & Mahoney, 2016; Zaki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…been examined in Scandinavia but has been addressed in several other international studies (Borre et al, 2015;Di Stefano et al, 2012;Mays, 1996;Miszkiewicz & Mahoney, 2016;Zaki et al, 2009).…”
mentioning
confidence: 99%
“…However, the findings demonstrate the complex and not so straightforward relationship between SES, sex, and lifestyle factors such as nutrition and physical activity. For example, Di Stefano, Boano, Rabino Massa, Isaia and Panattoni [ 28 ] and Borre, Boano, Di Stefano, Castiglione, Ciccone, Isaia et al [ 29 ] found that high-status individuals buried inside the San Michele Church, North-West Italy, had significantly lower BMD than individuals buried in the cemetery. A larger intake of dairy products, more sun exposure, and greater physical activity in the cemetery group were presumed to explain the observed pattern.…”
Section: Introductionmentioning
confidence: 99%